Effectiveness of Interactive Classroom Tool: A Quasi-Experiment in Assessing Students’ Engagement and Performance in Mathematics 10 using ClassPoint - Doris V Querido; Alberto D Yazon; Karen A Manaig; Victoria E Tamban; Sherwin B Sapin (Applied Quantitative Analysis, 2023)
Concerns about students' math skills have long existed on a global scale, the Philippines performed "significantly low" compared to all other participating countries in different achievement assessments. In addition, many students are showing signs of growing disengagement, particularly in mathematics. This is a significant matter since students' success and performance in mathematics may be at risk because of their lack of engagement. This study aimed to determine the effectiveness of the ClassPoint, an Interactive Classroom Tool, in enhancing students' engagement and performance in mathematics in face-to-face classes. The researcher utilized a quantitative quasi-experimental design, with 60 students as participants, covering the second quarter of Most Essential Learning Skills of Mathematics 10. Independent and Paired Samples t-test was employed to determine significant differences between formative test, posttest, and student engagement mean responses. The results showed that the students in the Experimental group who used the Interactive Classroom Tool performed better than the Comparison group who did not. The Experimental group showed a significant improvement in their performance, reaching a mastery level of 78% MPS, and a highly significant difference between the Comparison group in the independent t-test result. In addition, a paired t-test revealed that the interactive classroom tool considerably increased student engagement, as indicated by the significant difference in engagement scores between before and after the Interactive Classroom Tool was implemented. The study suggests that instructors may use Interactive Classroom Tool or ClassPoint as instructional materials to increase student participation and performance.